Top Management Teams in Family‐Controlled Companies: ‘Familiness’, ‘Faultlines’, and Their Impact on Financial Performance - Minichilli, Alessandro; Corbetta, Guido; MacMillan, Ian C. (Journal of Management Studies, 2010)
abstractThis article examines the affect of family management on performance of the company. We examine how familiness can provide further insights beyond the classical demographic measures of top management teams (TMTs) in explaining variations in firms' financial performance. We combine arguments on the ‘bright’ and ‘dark’ side of family involvement in the firm; we complement positive predictions on family involvement with negative predictions and develop family firm‐specific measures of TMTs' familiness. Results indicate that while the presence of a family CEO is beneficial for firm performance, the coexistence of ‘factions’ in family and non‐family managers within the TMT has the potential to create schisms among the subgroups and consequently hurt firm performance. We find support for a hypothesized U‐shaped relationship between the ratio of family members in the TMT and firm performance. Additional evidence related to interactions between firm listing and CEO type on firm performance is then presented and discussed.